Diaphragm Disease: A Paradox in the Intestine - Anwar, Dr Ali Zaid; Jawale, Dr Hemant M; Mishra, Dr Akshat; Mishra, Dr Rahul; Ram, Dr Shrinivas (International Journal of Innovative Research in Medical Science, 2019)
Diaphragm disease is a paradoxical disease entity related entirely to the bowel and not having involvement of diaphragm muscles. It is the formation of strictures in the bowel secondary to submucosal fibrosis which looks like the diaphragm and hence the term “Diaphragm disease”. It is seen in chronic NSAIDS (Non-steroidal anti-inflammatory drugs) users. It is a rare entity, leading to intestinal obstruction as a severe complication. Diagnosis of diaphragm disease is a diagnosis of exclusion and mostly done intraoperatively in patients presenting with subacute intestinal obstruction because the symptoms are non-specific and no gold standard investigation is available to diagnose it. Grossly diaphragm disease is formation of strictures in the intestinal wall, leading to obstruction due to narrowing of the wall lumen. Serendipitously stasis of food in the stricturous segment leads to formation of an enterolith, thus leading to subacute intestinal obstruction. A chance finding seen in chronic NSAIDS user’s is formation of enterolith secondary to stricture formation due to diaphragm disease leading to subacute intestinal obstruction.